Factors Associated with Self-Care Among Patients with Chronic Kidney Disease Undergoing Hemodialysis - Lena Lestari; Hendra Kusumajaya; Arjuna Arjuna (Inspirasi Foundation, 2027)
Introduction: Chronic kidney disease (CKD) is a progressive condition characterized by the kidneys' inability to maintain the body's internal homeostasis, resulting in the accumulation of metabolic waste products and fluid and electrolyte imbalances. According to the Bangka Belitung Islands Provincial Health Office, 5,534 cases of CKD were reported between 2021 and 2023, with 855 patients undergoing hemodialysis. Objective: This study aimed to identify factors associated with self-care among patients with chronic kidney disease undergoing hemodialysis at Bakti Timah Hospital, Pangkalpinang, in 2025. Methods: This quantitative study employed a cross-sectional design involving 159 patients with chronic kidney disease undergoing hemodialysis at Bakti Timah Hospital, Pangkalpinang, in 2025. Data were analyzed to determine the associations between knowledge, family support, gender, and self-care. Results: Knowledge (p < 0.001), family support (p = 0.010), and gender (p = 0.010) were significantly associated with self-care among patients with chronic kidney disease undergoing hemodialysis. Conclusion: Knowledge, family support, and gender were significantly associated with self-care among patients with chronic kidney disease undergoing hemodialysis. Improving patients' knowledge and strengthening family support may enhance self-care practices and contribute to better treatment adherence and health outcomes.